2009
DOI: 10.1080/10256010802522200
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced fluorescence spectroscopy of14N18O and its application to breath analysis

Abstract: Laser-induced fluorescence (LIF) spectroscopy is an efficient tool for the detection of low nitric oxide (NO) concentrations down to the parts per trillion (ppt) range. The isotopic selectivity of this method provides a broad potential of applications. . This transition has been used for an isotope specific online detection of 14 N 18 O from exhaled air. The detection limit for 14 N 18 O is 7.3 ± 1.8 ppt. With respect to 18 O-labelled drugs and amino acids this denotes a novel extension to NO research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Specific techniques used for ammonia quantification are laser induced fluorescence (LIF), cavity ring down spectroscopy (CRDS), tunable diode laser absorption spectroscopy (TDLAS), photoacoustic spectroscopy (PAS), and optical frequency comb cavity -enhanced absorption spectroscopy (OFC-CEAS). With LIF, detection of breath molecules as low as 10 ppt has been demonstrated with gases such as nitric oxide [69]. Recently, however, LIF has shown the capability for making qualitative measurements of ammonia [70].…”
Section: Laser Spectroscopymentioning
confidence: 99%
“…Specific techniques used for ammonia quantification are laser induced fluorescence (LIF), cavity ring down spectroscopy (CRDS), tunable diode laser absorption spectroscopy (TDLAS), photoacoustic spectroscopy (PAS), and optical frequency comb cavity -enhanced absorption spectroscopy (OFC-CEAS). With LIF, detection of breath molecules as low as 10 ppt has been demonstrated with gases such as nitric oxide [69]. Recently, however, LIF has shown the capability for making qualitative measurements of ammonia [70].…”
Section: Laser Spectroscopymentioning
confidence: 99%
“…A section of these measurements is displayed in figure 2. It could be shown that in certain areas of the spectra 15 N 16 O as well as 14 N 18 O can be observed without interference with the main compound 14 N 16 O [30]. Simulations for all three isotopologues have been performed with the program pgopher [32].…”
Section: Resultsmentioning
confidence: 99%
“…The combination of a 40 m 3 h −1 oil diffusion pump and a 150 L s −1 turbo molecular pump evacuates the spectrometer to a base pressure of 10 −6 mbar. A detailed description of the setup is given elsewhere [30].…”
Section: Detection Proceduresmentioning
confidence: 99%
“…The potential energy curves of the lower lying level of NO diatomic molecule are constructed using the Rydberg-Klein-Rees (RKR) method with the help of the Bound program of Foth et al [30] Those states are X 2 Π, a 4 Π, A 2 Σ, B 2 Π, and b 4 Σ − . The essential spectroscopic constants required to construct the potential energy curves are cited from the literature [10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and are listed in Table 1.…”
Section: Line Assignments and Dissociation Energy Of Nomentioning
confidence: 99%
“…[15] The fluorescence intensity spectra under applied electromagnetic waves with high resolution conduce to the understanding the electronic structure of NO molecule. [16][17][18] A prominent feature of the NO molecule is the fluorescence of the A 2 Σ-X 2 Π system by UV radiation in the atmosphere. [19] In addition, the observing of the emission spectrum of NO molecule by glow discharge excitation is an important tool for studying the chemistry of the atmosphere and the environmental pollution.…”
Section: Introductionmentioning
confidence: 99%